ANALYZING THE EFFECT OF CAPITAL STRUCTURE AND FIRM SIZE ON FIRM VALUE (CASE STUDY: COMPANY THAT LISTED IN LQ-45 INDEX PERIOD 2010-2014) - Bestariningrum, Nenggar (Sam Ratulangi University, 2015)
ABSTRACT This study aims to determine the effect of capital structure and firm size on firm value (case study: company that listed in LQ-45 index period 2010-2014). The quantitative method with multiple linear regression analysis techniques had used. 42 companies has a sample of this study. The result shows that capital structure and firm size simultaneously have positive and significant effect on firm value. While partially, capital structure have positive and significant effect on firm value and firm size have positive and significant effect on firm value. The determination of capital structure using the debt at a certain level as a funding source can increase the profitability and value of the company. While the size of the company shows that the company with the larger scale will be easier to obtain debt associated with the level of confidence of creditors to large corporations. Keyword: capital structure, firm size, firm value